{(x-y)/(根号x+根号y)}-(x+y-2倍根号xy)/(根号x-根号y)=?

来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 13:25:14
{(x-y)/(根号x+根号y)}-(x+y-2倍根号xy)/(根号x-根号y)=?{(x-y)/(根号x+根号y)}-(x+y-2倍根号xy)/(根号x-根号y)=?{(x-y)/(根号x+根号y)

{(x-y)/(根号x+根号y)}-(x+y-2倍根号xy)/(根号x-根号y)=?
{(x-y)/(根号x+根号y)}-(x+y-2倍根号xy)/(根号x-根号y)=?

{(x-y)/(根号x+根号y)}-(x+y-2倍根号xy)/(根号x-根号y)=?
((x-y)/(√x+√y))-(x+y-2√xy)/(√x-√y),分母有理化,第一个式子分母乘以√x-√y,又(x+y-2√xy)=(√x-√y)(√x-√y),所以原式等于√x-√y-(√x-√y)=0

((x-y)/(√x+√y))-(x+y-2√xy)/(√x-√y),分母有理化,第一个式子分母乘以√x-√y,又(x+y-2√xy)=(√x-√y)(√x-√y),所以原式等于√x-√y-(√x-√y)=0